Analiza kointegracyjna związków stóp zwrotu z akcji, inflacji oraz produkcji przemysłowej w Polsce w latach 1996-2004 - Czekaj, Karolina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The purpose of this paper is to present main theories explaining how changes in inflation rate influence stock prices. The second part of this paper contains an attempt to point out the relationship between inflation and stock prices quoted on the Polish stock market. The analysis was extended by including the real activity to better interpret the phenomenon observed on the Polish stock market. The method, which has been used to test the long-run relationship between variables, was the multivariate cointegration analysis (exactly the Johansen cointegration test has been implemented and multivariate VECM has been estimated). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 113-125